Ars conjectandi three hundred years on. Issue 3 (20th June 2013) - Edwards, Anthony
<x xml:space="preserve">Abstract</x> This year sees the 300th anniversary of Bernoulli's Ars conjectandi–The Art of Conjecturing. It transformed gamblers' "expectations" into modern mathematical probabilities. More importantly, it sets forth what Bernoulli called his "golden theorem"– the law of large numbers – which underpins the whole of statistical inference. Professor Anthony Edwards digs deep.